The Kinetic Study of Adenosine Deaminase Activity in Renal Failure Patients - Lutfia M. Hassan; Parween A. Ismahail (Kirkuk Journal of Science, 2011)
Serum adenosine deaminase levels was measured in patients with acute renal failure and compare them with the results of healthy individuals. Serum adenosine deaminase levels were found to be significantly higher in patient with acute renal failure than in healthy individuals (63±20.1U/L) and (28±9.2IU/L), respectively. The study was carried in optimum pH value (6.5) and optimum temperature 37ć by which enzyme possess highest activity, the activation energy (Ea) of the reaction (ES-Complex) formation was estimated.